(untitled) (Economics and region, 2016)
Addresses the problems of development of the enterprises of the meat-processing industry, in particular the contradiction between demand (possible directions of realization) and potential (destinations of their own production). The development of most of the enterprises of food industry of the country, primarily oriented on the current demand of the consumers, not the maximum use of their own possibilities, it does not always lead to the best result in the middle- and long-term period. The main activity of the packing enterprise is processing of poultry meat and production of meat half-finished products for further implementation of wholesale customers in supermarket chains and for export. Formed directions possible development-processing enterprise, as the ratio of the areas of implementation and production. Based on regression dependencies, forecast the volume of realization of products formed. Based on the estimation of the ratio of estimated values of volumes of realization and their yield performed express-estimation of directions of meat-processing enterprise. Defined by the perspective directions of development and measures to their intensification. Sales volume prediction is performed subject to the successful implementation of the proposed measures-processing enterprise.